Age Impacts the Burden That Reference Memory Imparts on an Increasing Working Memory Load and Modifies Relationships With Cholinergic Activity - Bernaud, Victoria E.; Hiroi, Ryoko; Poisson, Mallori L.; Castaneda, Arthur J.; Kirshner, Ziv Z.; Gibbs, Robert B.; Bimonte-Nelson, Heather A. (Frontiers in Behavioral Neuroscience, 2021)
Rodent aging research often utilizes spatial mazes, such as the water radial-arm-maze (WRAM), to evaluate cognition. The WRAM can simultaneously measure spatial working and reference memory, wherein these two memory types are often represented as orthogonal. There is evidence, however, that these two memory forms yield interference at a high working memory load. The current study systematically evaluated whether the presence of a reference memory component impacts handling of an increasing working memory load. Young and aged female rats were tested to assess whether aging impacts this relationship. Cholinergic projections from the basal forebrain to the hippocampus and cortex can affect cognitive outcomes, and are negatively impacted by aging. To evaluate whether age-related changes in working and reference memory profiles are associated with cholinergic functioning, we assessed choline acetyltransferase activity in these behaviorally-tested rats. Results showed that young rats outperformed aged rats on a task testing solely working memory. The addition of a reference memory component deteriorated the ability to handle an increasing working memory load, such that young rats performed similar to their aged counterparts. Aged rats also had challenges when reference memory was present, but in a different context. Specifically, aged rats had difficulty remembering which reference memory arms they had entered within a session, compared to young rats. Further, aged rats that excelled in reference memory also excelled in working memory when working memory demand was high, a relationship not seen in young rats. Relationships between cholinergic activity and maze performance differed by age in direction and brain region, reflecting the complex role that the cholinergic system plays in memory and attentional processes across the female lifespan. Overall, the addition of a reference memory requirement detrimentally impacted the ability to handle working memory information across young and aged timepoints, especially when the working memory challenge was high; these age-related deficits manifested differently with the addition of a reference memory component. This interplay between working and reference memory provides insight into the multiple domains necessary to solve complex cognitive tasks, potentially improving the understanding of complexities of age- and disease- related memory failures, optimizing their respective treatments.